The Role of the Sensorimotor System in the Athletic Shoulder - Myers, Joseph B. (2000)
OBJECTIVE: To discuss the role of the sensorimotor system as it relates to functional stability, joint injury, and muscle fatigue of the athletic shoulder and to provide clinicians with the necessary tools for restoring functional stability to the athletic shoulder after injury. DATA SOURCES: We searched MEDLINE, SPORT Discus, and CINAHL from 1965 through 1999 using the key words “proprioception,” “neuromuscular control,” “shoulder rehabilitation,” and “shoulder stability.” DATA SYNTHESIS: Shoulder functional stability results from an interaction between static and dynamic stabilizers at the shoulder. This interaction is mediated by the sensorimotor system. After joint injury or fatigue, proprioceptive deficits have been demonstrated, and neuromuscular control has been altered. To restore stability after injury, deficits in both mechanical stability and proprioception and neuromuscular control must be addressed. A functional rehabilitation program addressing awareness of proprioception, restoration of dynamic stability, facilitation of preparatory and reactive muscle activation, and implementation of functional activities is vital for returning an athlete to competition. CONCLUSIONS/RECOMMENDATIONS: After capsuloligamentous injury to the shoulder joint, decreased proprioceptive input to the central nervous system results in decreased neuromuscular control. The compounding effects of mechanical instability and neuromuscular deficits create an unstable shoulder joint. Clinicians should not only address the mechanical instability that results from joint injury but also implement both traditional and functional rehabilitation to return an athlete to competition.